DETERMINANTS GREEN MARKETING AND CSR ON GREEN PURCHASE INTENTION THROUGH GREEN BRAND IMAGE AT FORE COFFEE JABODETABEK REGION - Kayla Lyzandra; Elkunny Dovir Siratan (International Journal of Application on Economics and Business, 2026)
Growing public concern about environmental issues and sustainability has encouraged food and beverage companies to adopt eco-friendly strategies as a source of market differentiation. This study examines the effects of green marketing and Corporate Social Responsibility on green purchase intention, with green brand image serving as a mediating variable, in the context of Fore Coffee in Greater Jakarta. A quantitative approach was applied by involving 250 respondents living in Greater Jakarta who had never purchased Fore Coffee products. The respondents were selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with partial least squares structural equation modeling through SmartPLS 3.0 to test the direct and mediating relationships among the variables. The findings reveal that green marketing has a positive and significant effect on both green purchase intention and green brand image. Corporate Social Responsibility also shows a positive and significant influence on these two variables. In addition, green brand image positively and significantly affects green purchase intention and mediates the relationship between green marketing and green purchase intention, as well as between Corporate Social Responsibility and green purchase intention. These results indicate that green brand image plays an important role in converting environmental initiatives into purchase intention. This study contributes to the green marketing literature, particularly in the coffee retail sector in developing countries. Its novelty lies in focusing on prospective customers, rather than existing consumers, within a highly competitive urban coffee market.